Participatory design of a high-fidelity prototype of an essential learning curricular tool - Valente, Bianor (2023)
In the context of the AE.Maps project (IPL/2022/AE.Maps_ESELx) – Essential learnings: mapping to promote curriculum integration – this paper presents the design of a high-fidelity prototype of a tool to support preservice and in-service teachers, during curricular vertical and horizontal articulation. This tool should make it possible to query a database of Essential learning (EL), using a userfriendly interface. The four-stage double-diamond model was used to guide the participatory design process. In the discovery phase, through task analysis and focus group, involving 51 pre-service and in-service teachers, user needs regarding EL search were gathered. In the exploratory and definition phase, problems were explored and defined, while personas were created. In the development phase, sketches made by different participants were used to develop and explore solutions for a friendly interface. Moreover, during this phase, an Excel medium-fidelity prototype was implemented, and a high-fidelity prototype was iteratively designed in a participatory way.